Intraperitoneal and Subsequent Intravenous Vancomycin: An Effective Treatment Option for Gram-Positive Peritonitis in Peritoneal Dialysis - RJ, Barone; NS, Gimenez; L, Ramirez (Journal of Clinical Nephrology, 2017)
Intraperitoneal vancomycin absorption is higher when there is peritoneal inflammation, but the absorption decreases with recovery from peritonitis. Consequently, intraperitoneal maintenance doses are ineffective, reducing the rate of cure. Aim:To evaluate the outcome of Gram-positive peritonitis treated with intraperitoneal and subsequent intravenous vancomycin. Methods: In April 1996, we initiated a protocol for treating peritonitis caused by Gram-positive organisms using a 2-g intraperitoneal loading dose of vancomycin followed by intravenous vancomycin at 1 g twice in 5 days for coagulase-negative Staphylococcus and at 1 g three times in 5 days for Staphylococcus aureus. We analyzed episodes of Gram-positive peritonitis (coagulase-negative and S. aureus) and the efficiency of the treatment protocol in 113 patients undergoing peritoneal dialysis between 1 April, 1996 and 3 August, 2016. There were 6090 patient-months and the mean treatment lasted 54±44 months. The outcomes were evaluated as (1) complete cure, (2) relapsing peritonitis, (3) catheter removal for refractory peritonitis, and (4) death. Results: A total of 51 cases of coagulase-negative Staphylococcus peritonitis and 37 of S. aureus were seen in 46 of the 113 patients (40.7%). Of these, coagulase-negative Staphylococcus (92.15%) and 34 S. aureus peritonitis (91.89%) resolved. Conclusion:The response to treatment was very satisfactory.